Identifikasi Karakteristik Timbulan Sampah di Kecamatan Seberang Ulu I - Septiani, Indri; Putri, Mega Kusuma; Heldayani, Eni (Jurnal Pendidikan Geografi Undiksha, 2025)
Population growth is the main factor in the waste problem. The aim of this research is to identify the characteristics of waste generation. The research method used is a survey with a quantitative approach with the entire population of waste generation using purposive sampling techniques and using data collection techniques such as observation, questionnaires and documentation. Research data consists of identification, characteristics and extent of waste generation. The data analysis technique in this research uses formulas and rules in accordance with SNI 19-3964 of 1994. The results of the research show that the identification of the characteristics of waste generation found at the location consists of types of waste such as organic waste and inorganic waste. The type of waste found was organic waste such as dry leaves, tree branches and wood. Meanwhile, the types of inorganic waste in the picture include plastic bottles, plastic bags, Styrofoam, plastic drink cups, plastic straws, plastic detergent and used tires. The area of ​​waste generation is 13 location points which have different areas in each location with a distribution pattern that tends to be in the form of a Low Cluster.